INDONESIA STOCK EXCHANGE: THEORETICAL AND PHILOSOPHICAL ANALYSIS OF MUDHARABAH AND MUSYARAKAH CONTRACTS - Lubis, Mukhlis; Janwari, Yadi; Syafe`i, Rahmat (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This article is a theoretical and philosophical analysis of the implementation of the mudharabah contract and musyarakah contract on the Indonesia Stock Exchange. This study aims to reveal the theory and business philosophy underlying the two contracts and the significance of this study on the development of science in the Islamic capital market. The research method used involves reviewing literature from various relevant sources, including academic literature, books, journals, and regulations related to the Islamic capital market. In the theoretical analysis, the two contracts are studied as a form of partnership and fairness in doing business, with a mudharabah contract as a collaborative relationship between fund owners and fund managers, and a musharakah contract as a form of partnership based on capital contributions between business partners. In addition, this study also highlights the philosophical aspects of the implementation of the two contracts, with the ethics of responsibility and mandate being important moral values. The results showed that the mudharabah contract and musharakah contract reflect the spirit of equality and justice in the sharing of business results and risks, as well as the philosophy of sharing and mutual benefit in doing business. Overall, this analysis confirms that these two contracts are important foundations in shaping business ethics and philosophy in the Islamic capital market, with ethical principles such as responsibility, justice, and equality as strong moral values in directing business people to carry out economic activities with integrity and awareness of social responsibility. This research makes an important contribution to the development of science in the Islamic capital market and can be a foundation for strengthening ethical and fair business principles in the future.Keywords: mudharabah, musharakah, Islamic capital market, theoretical analysis, philosophical analysis.